Analisis Implementasi Manajemen Risiko UMKM Donat di Kota Tebing Tinggi - Aulia Hasanah; Chuzaimah Batubara (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
Aproach, which aims to get crucial risks that get high scores. There are so many donut makers who have spread across the city of Tebing Tinggi and some are still making donuts using a manual system or still making donuts by hand so that the production capacity is relatively high and there are low management problems including sales or marketing facts that cannot be established. And having professional expertise and not having a real or factual business license and from a problem that can be offered through a program offered in the form of production equipment assistance in the form of a machine in a donut maker that has advanced technology can help Sari Sari in completing quickly in making donuts. Through the implementation of training and the support of facilities for producing donuts so that the volume of donut production also increases rapidly and the quality of the donuts is still guaranteed with different fillings and can affect taste and health can also create flavors that attract people’s attention and make donuts more unique and interesting. With a donut maker, you can make donuts and increase the productivity of making donuts up to three times that of making donuts using a manual system.